An Overlooked Zoonotic Disease: Retrospective Evaluation of Q Fever Seropositivity with Clinical Findings - Fatma SIRMATEL; Selçuk KILIÇ; Oya KALAYCIOĞLU; Pınar BÜCÜK; Talat Oğulcan ÖZARSLAN; Tuğçe DAMARSOY; Hasan Tahsin GÖZDAŞ (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Introduction: Q fever is a zoonotic disease with a high seroprevalence in our region and a low awareness in our country. Patients who were diagnosed as having Q fever clinically, serologically, and radiologically during 2017-2020 were evaluated retrospectively and classified according to the organ involvement. Materials and Methods: The diagnosis was made according to the radiological, clinical and serological findings of the patient. The patients were distinguished as acute, acute/possible, and chronic/persistent according to phase I and phase II antibody titration. Serological studies were carried out via immune fluorescent method. Patients included in the study were evaluated in terms of age, gender, admission date, organ involvement, responses to treatment, and acute phase indicators. Results: A total of 107 patients were evaluated retrospectively. Sixty three patients (58.9%) were defined as having acute disease, 29 (27.1%) acute/possible disease and 15 (14%) chronic/persistent disease. Patients with acute disease were admitted to the hospital in winter, patients with acute/possible disease were admittedin summer/spring and patients with chronic/persistent disease in summer. Lung involvement was found in 45.8% of patients with positive Q fever serology, kidney involvement in 30.8%, neurological involvement in 29.9%, liver involvement in 22.4%, joint involvement in 18.7%, heart involvement in 5.6%, lymphadenomegaly in 4.7%, and bone involvement in 1.9%. Hepatic involvement was higher in patients with chronic/persistent disease (22.4%), while fever (39.7%) and muscle-joint pain (23.8%) were seen more frequently in patients with acute disease. There were no statistically significant differences in demographical data and levels of acute phase reactants. Conclusion: Since a non-routine test is used in the diagnosis of the disease, occupational exposure should be evaluated in complaints of unknown origin. The patients having unexplained organ involvement and elevated acute phase reactants should be examined serologically for Q fever, especially in endemic areas.